경제적 위기 상황에서 지식재산권의 증대가 기업의 회복탄력성에 미치는 영향 - 김민호; Minho Kim; 최상옥; Sang-ok Choi (지식재산연구, 2025)
본 연구는 2018년부터 2022년까지의 ‘기업활동조사’ 데이터를 바탕으로 지식재산권의 증대가 기업의 매출액과 종사자수 변화에 미치는 영향을 분석하고, 경제적 위기 상황에서의 회복탄력성을 분석하였다. 잠재성장모델을 활용한 분석 결과, 지식재산권의 증가는 경제적 위기 상황에서도 기업의 매출액과 종사자수 회복 속도를 유의미하게 향상시키는 것으로 나타났다. 특히, COVID-19와 같은 경제적 충격이 기업의 경영에 미친 영향을 고려할 때, 지식재산권이 기업의 회복력을 강화하는 데 중요한 역할을 한다는 사실이 확인되었다. 지식재산권을 보유한 기업들은 위기 이후 매출액과 종사자수의 회복이 더 빠르고 효과적으로 이루어졌으며, 이는 지식재산권이 기업의 안정성과 장기적인 성장 가능성을 높이는 데 기여한다는 중요한 시사점을 제공한다. 또한, 중소기업을 대상으로 한 분석에서도 유사한 경향이 나타났다. 지식재산권이 증가한 중소기업은 매출액과 종사자수의 회복 속도가 유의미하게 빨라졌으며, 이는 지식재산권의 증대가 중소기업의 회복력 강화를 위해 전략적으로 중요하다는 점을 강조한다. 본 연구는 지식재산권의 증대가 기업의 위기대응 및 회복력 증진에 미치는 긍정적인 영향을 명확히 규명하며, 정책 입안자들에게 지식재산권 확보 및 활용을 지원하는 정책의 필요성을 제기한다. This study analyzed the impact of intellectual property rights enhancement on changes in corporate sales and employment and business resilience during economic crises based on ”The Survey of Business Activities” data from 2018 to 2022. The results of the analysis using latent growth modeling revealed that an increase in intellectual property rights significantly improved the speed of recovery for corporate sales and employment, even during economic crises. In particular, considering the impact of economic shocks (e.g., COVID-19) on business management, intellectual property rights were confirmed to play a crucial role in strengthening corporate resilience. Companies with intellectual property rights demonstrated a faster and more effective recovery of sales and employment after the crisis, suggesting that intellectual property rights contribute to enhancing corporate stability and long-term growth potential. Similar trends were also observed in the analysis of small and medium-sized enterprises (SMEs). The results of this study showed that SMEs with increased intellectual property rights had significantly faster recovery rates in sales and employment, emphasizing the strategic importance of intellectual property rights enhancement in strengthening the resilience of SMEs. The study findings clearly identify the positive impact of intellectual property rights enhancement on corporate crisis responses and resilience improvement. They also suggest that policymakers must develop policies supporting the acquisition and utilization of intellectual property rights.